Detection and removal of Giardia spp. cysts and Cryptosporidium spp. oocysts by anaerobic reactors in Brazil. Issue 13 (7th June 2022) - Valdez, Fernanda Queiroz; Leite, Luan de Souza; Zanetoni Filho, José Antônio; Tango, Mariana Daniel; Daniel, Luiz Antonio
ABSTRACT: The discharge of raw wastewater into the environment can be a contamination source of Giardia spp. cysts and Cryptosporidium spp. oocysts. The UASB (Upflow Anaerobic Sludge Blanket) reactor is the most popular technology applied for wastewater treatment in Brazil, nevertheless there is little information concerning its capacity for (oo)cyst removal. In this context, this study investigated the occurrence and removal of Giardia spp. cysts and Cryptosporidium spp. oocysts by three different UASB reactors ( i.e. Reactor A, B, and C) treating different wastewater types. In the wastewater influent, the concentration varied from 493.3 to 14, 000 cysts·L -1 for Giardia spp. and from 'not detected' to 53.3 oocysts·L -1 for Cryptosporidium spp . . The (oo)cyst concentration increased after the anaerobic treatment in Reactors A and B, while Giardia spp. log-removal of 0.5 ± 0.2 was found in Reactor C. The increment in (oo)cyst concentration may happened due to the inefficacy for (oo)cyst removal by the specific UASB reactor and/or due to the reduction of matrix interference for reactor effluent samples in the detection method. The results suggest that hydraulic retention time (HRT) may be the key parameter for Giardia spp. removal by the UASB reactor. Furthermore, no parameter analysed (physical-chemical and indicator microorganisms) showed a common correlation with the (oo)cyst concentration in the three UASB reactors. Considering that official data of cryptosporidiosis and giardiasis cases are rarely reported in Brazil, monitoring Giardia spp. cysts and Cryptosporidium spp. oocysts in wastewater could be an alternative to estimate the occurrence of diseases in the served population. GRAPHICAL ABSTRACT: UF0001